CHARACTERISTIC OF NATURAL CARBON NANOMINERALS AND THEIR AGGREGATES FROM THE DZHARAKUDUK AREA (UZBEKISTAN) - M.Yu. Povarennykh; E.N. Matvienko; A.V. Knot′ko; T.B. Shatalova (Минералогия, 2018)
Interstitial fibrous nanoscale aggregates of multilayered carbon nanotubes, fullerenes, and fullerenoids were found in quartz and potassium feldspar grains of slag-like rocks (metamorphosed polymictic sandstones) of the Dzharakuduk area (Kyzylkum Desert, Uzbekistan). This is the first find of carbon nanotubes ~10 Å in diameter and their assemblages in natural rocks. Based on high-resolution transmitting and scanning electron microscopy, Raman spectroscopy and MS DTA, it is shown that carbon fullerenes are from 1–2 to 30–50 nm in diameter and carbon nanotubes are distinct in diameter (1–3 to 40–60 nm), length (7–10 to few hundreds of nanometers), and the amount of layers (2–3 to 40). Owing to electron transparency of carbon nanominerals and their magnification in one million times, we revealed morphological features of their zonal-sectorial structure and cut evolution.